A qualitative inquiry on religious married men's perceptions of relationship dynamics during everyday sickness. (September 2021) - Novak, Josh R; Johnson, Adam; Gast, Julie; Peak, Terry; Arnell, Melinda
The purpose of this study was to evaluate men's perceptions of self-dynamics and partner dynamics during common everyday sickness. Five focus group interviews ( N  = 44) were conducted, each lasting approximately 120 minutes. The data were analyzed using a generic qualitative approach which identified two larger themes and several sub-themes: sickness appraisals and appraisal communication (gender differences in symptom appraisal and minimization of own and partner's sickness) and coping and support strategies (individual coping, one-way provision of support, and coping together). It seems acute sickness creates shared stressors for both partners but differentially impacts each based on gender and family roles.